Frequency of Cardiac Arrhythmias in Hypertensive Patients - Muhammad Naeem Tariq; Naseer Ahmed Samore; Muhammad Humayoun Rashid; Sohail Aziz; Ghoza Chaudhery; Jahanzab Ali; Naseem Azad; Ahmad Noeman; Syeda Neelam Yamin Bukhari; Azhar Ali Chaudhry (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the frequency of cardiac arrhythmias in hypertensive patients.